2014
DOI: 10.1242/jcs.113233
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient-driven O-GlcNAc cycling – think globally but act locally

Abstract: Proper cellular functioning requires that cellular machinery behave in a spatiotemporally regulated manner in response to global changes in nutrient availability. Mounting evidence suggests that one way this is achieved is through the establishment of physically defined gradients of O-GlcNAcylation (O-linked addition of Nacetylglucosamine to serine and threonine residues) and OGlcNAc turnover. Because O-GlcNAcylation levels are dependent on the nutrient-responsive hexosamine signaling pathway, this modificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 141 publications
1
53
0
3
Order By: Relevance
“…All percents are the % of pol II peaks either at promoters or in gene bodies. by nutrient flux, as glucose, glutamine, acetyl CoA, and UTP are all necessary for UDP-GlcNAc biosynthesis (35,67). It is likely though that the UDP-GlcNAc is not the only component of the nutrient-sensing mechanism.…”
Section: Tablementioning
confidence: 99%
“…All percents are the % of pol II peaks either at promoters or in gene bodies. by nutrient flux, as glucose, glutamine, acetyl CoA, and UTP are all necessary for UDP-GlcNAc biosynthesis (35,67). It is likely though that the UDP-GlcNAc is not the only component of the nutrient-sensing mechanism.…”
Section: Tablementioning
confidence: 99%
“…The other major O-GlcNAcase isoform has a 14-amino extension that serves to target it to lipid droplets. This O-GlcNAcase isoform is involved in the remodeling of lipid droplet surface proteins by local activation of proteasomes on the lipid droplet surface (38,42). This study suggested a nexus between the regulation of lipid storage and hexosamine signaling through O-GlcNAc cycling (42).…”
mentioning
confidence: 90%
“…The mOGT and sOGT variants contain 9 and 2 TPR, respectively (37). The TPR mediate interaction with a large number of effector proteins that target or regulate OGT (38,39). It is likely that the TPR also serve a scaffolding function, distinct from any role in enzymatic activity (38).…”
Section: The Enzymes Of O-glcnac Cyclingmentioning
confidence: 99%
See 2 more Smart Citations